A pedagogical project from the perspective of Critical Mathematical Education with active methodologies - Liziane Borges Fagundes; Ana Carolina Staub de Melo (Universidade Federal do Oeste da Bahia, 2020)
The present study, bibliographic, descriptive and propositive, aims to present a pedagogical project in the light of critical mathematical education with the use of active methodologies within the scope of Youth and Adult Education. When problematizing mathematical education for young, adult and elderly people, we identified that in this educational context there is a need to promote emancipatory pedagogical proposals, where the use of active methodologies qualifies the teaching-learning process. In this sense, it is understood that the teaching of mathematics enables active and participative ways of teaching and learning, where students can take the lead in the educational process. Throughout the text we seek a dialogue with different authors who deal with the educational perspective developed here. The designed project, although feasible in the school context of EJA, should be implemented and its results analyzed in later works.